PECULIARITIES OF THE KRASNODAR REGION’S TEENAGERS’ NEUROLOGICAL STATUS - E. I. Kleshenko; D. A. Kayumova; M. G. Kulagina; E. V. Borovikova; E. P. Apalkova; L. M. Kravchenko; M. P. Yakovenko (Кубанский научный медицинский вестник, 2017)
The aim of this scientific work is detecting of neurological pathology among first grade students. We examined 2507 students (1414 male and 1093 female) in the age from 16 to 18 in the process of deep medical examination. We collected neurological complains, neurostatus, analyses of medical documentation. This data was statistically handled. Therefore 80% of students had neurological pathology. The most frequent cases were vegetative-vascular dystonia, vertebrogenic pathology and essential headache. The gained data means the very high level of neurological disease among students, which shows not only importance of rehabilitation activities, but modernization of preventive activities among adolescences.